2022
DOI: 10.1038/s41598-022-18470-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of behavioral and psychological symptoms of Alzheimer’s disease on caregiver outcomes

Abstract: This study was to determine the prevalence of behavioral and psychological symptoms of dementia (BPSD) and its association with dementia severity and to explore the association between specific BPSD and caregiver stress, burden, and depression. A cross-sectional study involving the interviewing of the primary caregivers of patients with Alzheimer’s disease (AD) was conducted. Multivariable analysis was used to analyze the associations between specific symptoms of BPSD and caregiver outcomes. A total of 102 AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Additionally, the sex of participants was 75% (n=15) female, which may yield different insights compared with settings with varying sex ratios among caregivers. However, in Thailand, the majority of caregivers for older adults are female, with a prevalence ranging from 70% to 90% [43][44][45]. This ratio is similar to that in our study.…”
Section: Limitationssupporting
confidence: 89%
“…Additionally, the sex of participants was 75% (n=15) female, which may yield different insights compared with settings with varying sex ratios among caregivers. However, in Thailand, the majority of caregivers for older adults are female, with a prevalence ranging from 70% to 90% [43][44][45]. This ratio is similar to that in our study.…”
Section: Limitationssupporting
confidence: 89%
“…Caregivers to persons living with AD/ADRD must also manage behavioral and psychological symptoms of dementia (BPSD), characterized by disturbances in mood and behavior that affect nearly all persons living with AD/ADRD (10). BPSD are positively associated with both caregiver burden and depressive symptomology and contribute to resistance to care from care recipients (11,12). Communication challenges add another layer of di culty when delivering complex care to persons living with AD/ADRD, as care recipients may be unable to communicate their needs or express pain (4).…”
Section: Funding {4}mentioning
confidence: 99%
“…AD has a greater impact on the patients’ quality of life and function. It is observed that the rate of health service utilization among AD patients is very high and patients go through more falls and accidents as compared to age-matched controls [ 5 , 6 ]. With continuous decline in their independence, the person with AD puts large financial, psychological and physical burden on their family caregivers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%